2021
DOI: 10.25004/ijpsdr.2021.130517
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential anti-dengue lead from Nilavembu through in silico study

Abstract: Dengue fever is a severe mosquito-borne global health concern caused by the Dengue virus. There are no effective vaccines or anti-virals against dengue, even though several medications are under developmental stages. As we all know, the traditional medicine system mainly depends on plants to treat various types of diseases caused by bacteria, viruses, and other micro-organisms. In this scenario, the present study focussed on identifying the inhibitory potential of phytoconstituents from a well-known antipyreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…An in silico study of phytoconstituents of Nilavembu Kudineer revealed that oleanolic acid has potential inhibitory activity against NS-5 methyltransferase of DENV [32]. In addition, a molecular docking study found that the andrographolide of A. paniculata has potential inhibitory activity against envelope protein and NS-5 methyltransferase of DENV [33].…”
Section: Andrographolidementioning
confidence: 99%
“…An in silico study of phytoconstituents of Nilavembu Kudineer revealed that oleanolic acid has potential inhibitory activity against NS-5 methyltransferase of DENV [32]. In addition, a molecular docking study found that the andrographolide of A. paniculata has potential inhibitory activity against envelope protein and NS-5 methyltransferase of DENV [33].…”
Section: Andrographolidementioning
confidence: 99%